A revision of the genus Pachygrapsus Randall, 1840 (Crustacea: Decapoda: Brachyura, Grapsidae), with special reference to the Southwest Pacific species - Poupin, Joseph; Davie, Peter J.f.; Cexus, Jean Christophe (Zootaxa, 2005)
The genus Pachygrapsus Randall, 1840 is revised with particular attention to the five Southwest Pacific species: P. fakaravensis Rathbun, 1907, P. laevimanus Stimpson, 1858, P. minutus A. MilneEdwards, 1873, P. planifrons De Man, 1888, and P. plicatus (H. Milne Edwards, 1837). Pachygrapsus laevimanus Stimpson, 1858 is redescribed and a neotype is designated because of confusion of this species with P. transversus (Gibbes, 1850). Seven other species were examined: P. corrugatus (von Martens, 1872), P. crassipes Randall, 1840, P. gracilis (de Saussure, 1858), P. loveridgei Chace, 1966, P. marmoratus (Fabricius, 1787), P. maurus (Lucas, 1846), and P. transversus (Gibbes, 1850). The type specimens of P. striatus A. Milne-Edwards, 1873, and P. laevis Borradaile, 1900, were re-examined and found to be junior synonyms of P. plicatus (H. Milne Edwards, 1837), and P. planifrons De Man, 1888, respectively. Pachygrapsus kraussii (Dana, 1852) is considered a junior synonym of P. plicatus H. Milne Edwards, 1837. Pachygrapsus polyodous Stebbing, 1921, is excluded from Pachygrapsus and provisionally placed in Euchirograpsus H. Milne Edwards, 1853. Pachygrapsus propinquus De Man, 1908, is probably a junior synonym of P. minutus A. MilneEdwards, 1873, but its status needs to be confirmed with the collection of new material from the type locality. Pachygrapsus now includes twelve species, thirteen if P. propinquus De Man, 1908, proves to be a separate species. A key to all thirteen species is given.